Controlling bacterial biofilm formation by native and methylated lupine 11S globulins - Enan, Gamal; Abdel-Shafi, Seham; El-Nemr, Mona; Shehab, Wesam; Osman, Ali; Sitohy, Mahmoud; Sitohy, Basel (Frontiers in Microbiology, 2023)
Abstract The antibacterial and antibiofilm activities of the 11S globulins isolated from lupin seeds (Lupinus termis), and its methylated derivative (M11S), were investigated against seven pathogenic Gram-positive and Gram-negative bacteria. The MIC of 11S ranged from 0.1-4.0 μg/mL against 0,025-0.50 μg/mL for M11S, excelling some specific antibiotics. The MICs of M11S were 40-80 times lower than some specific antibiotics against Gram-positive bacteria and 2-60 times lower than against Gram-negative bacteria. One MIC of 11S and M11S highly reduced the liquid growth of all tested bacteria during 24 h at 37 °C. They also inhibited biofilm formation by 80-86% and 85-94 %, respectively (Gram-positive) and 29-44 % and 43-50 %, respectively (Gram-negative). M11S prevented biofilm formation by Gram-positive bacteria at minimum biofilm inhibitory concentration (MBIC); 0.025- 0.1 µg/mL against 0.1- 0.5 µg/mL for Gram-negative bacteria, i.e., 4-20 times and 4-7 times antibiofilm inhibitory action compared to 11S, respectively. Biofilm formation of two bacteria on glass slides for 24 h at 37°C revealed no adhered cells, i.e., was entirely prevented by one MBIC of 11S and M11S. Scanning electron microscopy indicated microbial biofilm deformation under the action of 11S and M11S, indicating their broad specificity and cell membrane-targeted action.